Improving the Efficiency of Modular-Credit Training Using Information and Communication Technologies - Alimova Kamola Mirshahidovna (Researchparks Publishing, 2022)
The article describes problems related to improving the efficiency of modular-credit training using information and communication technologies. The task of the teacher at the present stage of educational development lies in creating conditions for the realization of the creative potential of each learner. The main goal today is not to give the greatest amount of knowledge, but to ensure general cultural, personal, cognitive growth. The practical consequence of the introduction of information technology in the learning process is: improving the organization of teaching, increasing the individualization of learning; increasing the productivity of self-training of students; individualization of the work of the teacher himself; acceleration of replication and access to the achievements of pedagogical practice; strengthening motivation for learning; activation of the learning process, the possibility of involving students in research activities; ensuring the flexibility of the learning process.